Impact of target coronary artery stenosis severity measured by instantaneous wave-free ratio on to bypassed graft patency - Almas Tolegenuly; Arslan Mamedov; Rimantas Benetis (National Scientific Medical Center, 2021)
Background: This study aimed to assess the impact of the measurement of the degree of target coronary artery stenosis using the instantaneous wave-free ratio (iFR) on patency of attached grafts. Materials and Methods: A total of 86 grafts were assessed by computed tomography angiography (CTA) after coronary artery bypass grafting (CABG) in 24 patients with multivessel coronary artery disease (CAD). The iFR was evaluated for all target coronary arteries. The coronary artery stenoses were divided into three groups based on the iFR value: iFR < 0.86 (group 1); iFR 0.86-0.90 (group 2); and iFR > 0.90 (group 3). Results: CTA was performed at 192 ± 44 days (range: 80-318 days). The correlation coefficient (r) between iFR and failed grafts was 0.332 (p = 0.035). Graft failure was detected in three grafts (8.1%) for group 1, in two grafts (8.3 %) for group 2, and in four grafts (16%, all arterial grafts) for group 3. Statistically significant differences were found between groups 1 and 3 (p = 0.041) and between groups 2 and 3 (p = 0.044). No significant differences were found between groups 1 and 2 (p = 0.228). Conclusions: The degree of coronary artery stenosis measured by iFR is a risk factor for attached graft failure. In a coronary artery where the iFR was haemodynamically non-significant, a higher rate of graft failure was detected.